PENGEMBANGAN MODUL AJAR BERBASIS PROBLEM BASED LEARNING DALAM BENTUK FLIPBOOK UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS - Amaliyah, Dina Inti; Purwoko, Riawan Yudi; Kurniawan, Heru; Wibowo, Teguh (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2023)
The research was conducted to determine the validity, practicality, and validity of problem-based learning teaching modules in the form of flipbooks to improve students' critical thinking skills in Phase E. The type of research used was research and development (RD) using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this study were class X students (Phase E) and educators at SMA N 1 Prembun. Data was collected using interviews, questionnaires, and test questions. Interview sheets, validation questionnaires, practicality questionnaires, and test questions were used as instruments in this study. The data obtained were then analyzed using descriptive analysis. The results of this study indicate that the problem-based learning module in the form of a flipbook will improve students' critical thinking skills in Phase E concentration. 1) is valid with a yield proportion of 80%; 2) practical for educators with a proportion yield of 86%; and 3) effective with an n-gain score of 0.78. Based on this, problem-based learning modules in the form of flipbooks to improve students' critical thinking skills in Phase E can be used in educational units with appropriate characteristics. The use of flipbooks is not limited to student worksheets; all independent curriculum modules are in flipbooks.